2020
DOI: 10.3389/fbioe.2020.614510
|View full text |Cite
|
Sign up to set email alerts
|

Improving Biological Treatment of Real Bilge Wastewater With Zero Valent Iron and Activated Charcoal Addition

Abstract: From the ships engine rooms a recalcitrant wastewater is produced called “bilge” which contains oil, metal working fluids, surfactants, and salinity. This study investigated the treatment of real bilge wastewater in short experiments using the following processes: (i) anaerobic digestion with granular sludge and ZVI addition for enhancement of methane production, (ii) activated charcoal addition to biological treatment (aerobic and anaerobic) for Chemical Oxygen Demand (COD) significant reduction and (iii) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Mazioti et al . reported the anaerobic treatment effect of adding ZVI or active carbon to the anaerobic system alone and adding ZVI and activated carbon at the same time to treat real bilge wastewater 24 . The results showed that the simultaneous addition of iron and carbon could achieve more efficient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Mazioti et al . reported the anaerobic treatment effect of adding ZVI or active carbon to the anaerobic system alone and adding ZVI and activated carbon at the same time to treat real bilge wastewater 24 . The results showed that the simultaneous addition of iron and carbon could achieve more efficient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, biological methods, progressively gain interest in treating saline wastewaters rich in organic content and petroleum hydrocarbons [9] using microorganisms able to consume such compounds [10]. However, biological activity may be strongly inhibited by the hostile nature of the recalcitrant wastes such as BW [11]. Therefore, the use of indigenous species or species adapted to recalcitrant wastewater is proved more advantageous over non-native micro-organisms for achieving better results.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of bilge water with a moving bed biofilm reactor has been studied, and the greatest obtained COD removal efficiency was as 86% [21]. Mazioti A.A. et al [22] investigated the treatment of bilge water by anaerobic digestion via granular sludge, and they reported that methane production and COD removal efficiency significantly increased after adding zero valent iron and activated charcoal, respectively. In addition, the removal efficiency of organic materials differed in the range of 36.2-71% when electrochemical processes such as electrocoagulation and electro-Fenton were applied for bilge water treatment [4].…”
Section: Introductionmentioning
confidence: 99%